Influence of ABCB1 Gene Polymorphism on Rivaroxaban Blood Concentration and Hemorrhagic Events in Patients With Atrial Fibrillation - Wang, Yan; Chen, Min; Chen, Hui; Wang, Fang (Frontiers in Pharmacology, 2021)
Background and objectives: Genetic data on the pharmacokinetics of rivaroxaban and identification of factors that affect its biotransformation, distribution, and excretion will allow for generation of algorithms for personalized use of this drug in patients with atrial fibrillation (AF). Here we tested the effects of ABCB1 （ATP-binding cassette subfamily B member 1）polymorphisms on the rivaroxaban blood concentration and on the frequency of hemorrhagic events in patients with AF and propose a personal anticoagulation therapy management protocol. Patients and methods: This was a retrospective, multicenter, observational study. We enrolled patients who met the criteria for admission and discharge from May 2018 to August 2018. We collected clinical data on gender, height, weight, liver, and kidney functions, drug trough concentration, and drug dosage; we also recorded bleeding events until 6 months after initiating the medication. We collected 4.5 mL blood samples to measure Xa and rivaroxaban plasma concentrations. We identified ABCB1 single nucleotide polymorphisms including rs1128503 (1236C > T, Gly412Gly), rs1045642 (3435 C > T, Ile1145Ile), and rs4148738. Results: We included 97 patients in this study including 70 men and 27 women, with an average age of 71.21 ± 11.36 years. The distribution of ABCB1 genotypes conformed to the Hardy–Weinberg equilibrium. Multiple comparisons between wild (TT) and mutant (CT and CC) genotypes at the rs1045642 locus showed no significant differences of rivaroxaban concentrations (TT vs. CT, p = 0.750; TT vs. CC, p = 0.869; CT vs. CC, p = 0.546). Multiple comparisons between wild (TT) and mutant (CT and CC) genotypes at the rs1128503 locus revealed significant differences of rivaroxaban concentrations (TT vs. CT, p = 0.050; TT vs. CC, p = 0.035; CT vs. CC, p = 0.785). Multiple comparisons between wild genotype (GG) and mutant (AG and AA) genotypes at the rs4148738 locus showed no significant differences of rivaroxaban concentrations (GG vs. AG, p = 0.105; GG vs. AA, p = 0.355; AG vs. AA, p = 0.325). Conclusion: rs1128503 locus variations are correlated with the serum concentration of rivaroxaban in patients of Mongolian descent but not with the occurrence of bleeding events in the same individuals.